A Homozygote Mutation in S-Antigen Visual Arrestin SAG Gene in an Iranian Patient with Oguchi Type One: A Case Report - Hajar ARYAN; Atekeh BAHADORI; Dariush D. FARHUD; Marjan ZARIF YEGANEH; Haniyeh POURKALHOR (Tehran University of Medical Sciences, 2020)
Oguchi disease is a rare autosomal recessive form of congenital stationary night blindness (CSNB) characterized by specific features such as golden-brown discoloration of the fundus called Mizuo-Nakamura phenomenon which is distinguishable by fundoscopy, and retinography. Clinical diagnosis is confirmed through genetic test. Two known genes in pathogenesis of Oguchi disease are SAG and GRK1. A 35-year-old Iranian male exhibiting the clinical features of congenital stationary night blindness, was referred to the genetic clinic of Dr. Farhud, Tehran, Iran in 2012 and examined. Ophthalmic examination including slit-lamp biomicroscopy, perimetry and funduscopy was performed. Additionally, the full-field electroretinography and molecular testing for congenital stationary night blindness were performed. Molecular genetic tests, including the analysis of GSK1 and SAG genes exon-intron boundaries were performed for this patient and his family. According to the sequencing results, we did not find any mutation in GSK1 gene. However, a new homozygote mutation at location chr2:233320735, c.517delC, p.P96LfsX28 was identified in exon four of SAG gene. This deletion causes a frame shift mutation, and premature stop codon that results in deletion of about 281 amino acid residues of S-antigen visual arrestin protein (from entire C-terminal). This mutation was also found in patient's parents and one of his sister as heterozygote form. This is the first molecular evidence for SAG gene mutation in an Iranian family affected with Oguchi disease type 1. The identification of the new c.517delC, p.P96LfsX28 mutation in this family with Oguchi disease can confirm the pathogenicity of this variant.